Acral vascular syndrome during an immune checkpoint inhibitor. Issue 5 (17th May 2020) - O'Connor, Patrick; Bhadbhade, Pooja; Khan, Qamar; Williamson, Stephen
Abstract : Immune checkpoint inhibitors, including antiprogrammed death cell protein 1 (anti-PD-1) and anti cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4), have been associated with a range of autoimmune-related side effects since their introduction in cancer treatment. Small vessel digital necrosis, referred to as the acral vascular syndrome, is a rare but serious complication that can result in loss of digits. Here we present a case report of acral vascular syndrome and review possible aetiologies. A 45- year-old woman with invasive ductal carcinoma of the left breast presented to the emergency department during neoadjuvant treatment with carboplatin, docetaxel and pembrolizumab with complaints of severe pain in her right third digit. She had physical findings consistent with ischaemic necrosis and gangrene of the distal phalanx. Angiography demonstrated Raynaud's phenomenon in the distal portion of the digits. Laboratory testing showed a weakly positive RNA polymerase III antibody level. Her case resulted in surgical amputation of her affected digit after partial resolution of symptoms with prednisone, vasodilators and antibiotics.